Kognisi dan Keseimbangan Tubuh : Studi pada Populasi Lanjut Usia - Syahbana, Ali; Rudiyanto; Ayu Putu Linda Purnama Dewi, Ida (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: The aging process is part of the final stage of life, and a decline in physiological function characterizes it. A decline in physiological function will affect the elderly organ systems. Physical stability are influenced by cognitive decline, so that the elderly often have difficulty in carrying out daily activities, tend to be easily unsteady, stumble, and fall. This study aimed to identify the relationship between cognitive function and body balance in older people. Methods: The design of this study used a cross-sectional approach. The number of respondents in this study was 27 older adults. The sampling technique used was Cluster Sampling. The data collection instruments in this study were the Mini-Cog and Clock Drawing Test for cognitive function and the Berg Balance Scale (BBS) for the elderly's body balance. Data analysis was done using the Spearman Rank correlation test with SPSS 27. Results The results showed that the category of cognitive function with a high probability of cognitive impairment was 18 respondents (66.7%), and body balance in the walking with assistance category was 19 respondents (70.4%). The statistical analysis results show a p-value = 0.001 (p < 0.05), a Rho value of 0.641, which means that cognitive function strongly relates to body balance Conclusion: Cognitive function in the elderly can be maintained in prime condition with various interventions such as early screening and regular physical training for maintaining body balance.